Visceral leishmaniasis infection stimulates anxiety behaviour and social behaviour disorders in rat models - Imran, Rania Hayder; Chabuk, Halla Abdul-Hadi; al-Hassnawi, Alaa Tareq Shakir (Iraqi Journal of Science, 2026)
Leishmaniasis, a tropical disease caused by different species of Leishmania parasites, spreads through the bite of the female sand fly. Visceral Leishmaniasis (VL) is the most severe manifestation of Leishmaniasis. If untreated, it can lead to a high fatality rate. This research was designed to examine the prospects of alterations in behavior that might arise following an infection of visceral leishmaniasis in rats. This was achieved by evaluating the exploratory or locomotor activity, anxiety levels, and emotional social behaviour of infected rat models. Sixty adult  male Wistar rats were divided into four groups: a control group and three infected groups with (10, 50, and 100 million parasites). Behavioural experiments were conducted for two, four, six, eight, and 10 weeks following the injection of visceral leishmaniasis, using an open field test and a social behaviour test. The results indicated a rise in anxiety-related behaviour and a reduction in locomotor activity, as evaluated by the open field test. Furthermore, the results demonstrated an increase in depression, as determined by the social behaviour test. Infection with Leishmania donovani increases anxiety-like behaviour, decreases emotion-related social activities and communication, and reduces locomotion. These observations were made using typical behavioural tests like open field and social behaviour assessments.